Psychogenic facial pain: presentation and treatment. Issue 6415 (11th February 1984) - Feinmann, C; Harris, M; Cawley, R
Abstract : Ninety three patients took part in a two centre double blind controlled clinical trial designed to assess the efficacy of dothiepin (Prothiaden) as compared with placebo and a soft biteguard in the treatment of psychogenic facial pain. The results showed the superiority of dothiepin over placebo in achieving pain relief; 71% of patients were pain free in the dothiepin group at nine weeks compared with 47% in the placebo group. The biteguard conferred no benefit and compliance in its use was poor. Out of 84 patients followed up for 12 months, 68 (81%) became pain free. An adverse life event before development of pain, minimal previous surgical treatment, and freedom from pain at nine weeks were strong prognostic indicators for successful treatment. These results are clear evidence of the efficacy of dothiepin in psychogenic facial pain, though the drug may be needed for up to a year.